THE IMPACT OF MARKET AND BRAND ORIENTATION ON PERFORMANCE: AN EMPIRICAL STUDY - AYAR, BAHADIR (FUTURE ACAD, 2017)
The aim of this study is to investigate the effects of market orientation and brand orientation on firm performance. An integrative approach is used in designing the research model. Market orientation and brand orientation taken as antecedents of firm performance are included in the model as existed in the literature. However, researches on how companies become market-oriented, brand-oriented and how market orientation and brand orientation affect firm performance are still rather limited. Therefore, the aim of this paper is to propose a theoretical model showing what factors contribute to market orientation and brand orientation, as well as the their effect on firm performance for Turkish brands. Variables in the proposed research model were measured by scales already existed in the literature. A questionnaire form is used via both online and face-to-face interviews for gathering data in the survey. Data were collected from the firms which are members of United Brand Association with 144 firms. The universe of the research consists of the marketing manager, the brand manager and / or the corporate communications managers of the companies that are members of the United Brands Association. This paper also demonstrates a value for its sectoral brands-specific findings. (C) 2017 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Market orientation; brand orientation; brand image; brand performance firm performance; Turkish brands; ANTECEDENTS; STRATEGY; FIRMS; SMES